Dietary grape pomace extract supplementation improved meat quality, antioxidant capacity, and immune performance in finishing pigs - Tian, Xuekai; Li, Dong; Zhao, Xin; Xiao, Zitong; Sun, Jingchun; Yuan, Tiantian; Wang, Yongcheng; Zuo, Xinhui; Yang, Gongshe; Yu, Taiyong (Frontiers in Microbiology, 2023)
In pig production, reducing production costs and improving immunity are important. Grape pomace, a good agricultural by-product, has been thrown away as food waste for a long time. Recently, we found that it could be used as a new source of pig feed. We investigated the effect of grape pomace on inflammation, gut barrier function, meat quality, and growth performance in finishing pigs. Our results indicated that treatment samples showed a significant decrease in water loss, IL-1β, DAO, ROS, and MDA content (p < 0.05). IgA, IgG, IgM, CAT, T-AOC, SOD, and IFN-γ significantly increased compared with those in control samples (p < 0.05). Meanwhile, the relative mRNA expression of the tight junction protein occludin showed a significant difference (p < 0.05). Analysis of metagenomic sequencing indicated that grape pomace significantly decreased the relative abundance of Treponema and Streptococcus (p < 0.05). In summary, our results demonstrated that grape pomace could improve meat quality, alleviate inflammation, and decrease oxidative stress.